Open Banking Ecosystem : The Indian Perspective - Patki, Aarti; Sople, Vinod (Indian Journal of Finance, 2022)
The financial services industry has globally witnessed rapid changes because of technological advances. Banks started sharing customer information with customer consent but under regulatory guidelines to meet the changing customer demands and market competition. This situation enabled the banking industry to open its IT infrastructures, leading to the following level of banking services: open banking (O.B.). Due to technological advancement, banks and fintech companies started partnering to create innovative financial products/services for meeting customer requirements. Indian banks, in line with their global counterparts, are also in the race. The leading banks like Federal Bank, Yes Bank, ICICI Bank, and RBL Bank have taken open banking ecosystem growth initiatives over the last few years. Many other Indian banks and NBFCs have taken steps to be a part of the O.B. ecosystem. They have made a lot of investments on the technology front and made changes in their organizational culture to meet the new challenges. This paper discussed the implementation status of open banking, APIs, customer data rights, the liability of banks, regulatory framework, and implementation capability of banks. It also covered the implementation journey and its success.